SERANGAN KUMBANG AMBROSIA PLATYPUS TREPANATUS PADA DOLOK RAMIN - Paimin Sukartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The infestations of ambrosia beetle Platypus trepanatus Chap. (Coleoptera: Platypodidae) on felled ramin trees (Gonystylus bancanus Kurz.) were studied in a logging area of West Kalimantan. Three felled ramin trees, d.b.h, approximately 25 cm, were prepared for the beetle infestations on their felling sites for 20 days. Six sections of each trunk, each of 0.5 m length, which were consecutively arranged at intervals 2.0 m started from the basal, were observed. Number of the beetle tunnels on each trunk section were counted, and diameter, area of surface, and volume of the trunk sections, were measured.More tunnels were found on the larger diameter of trunk sections. However, analyses of the data showed no discernible trends for the intensity of the beetle attacks in different trunk sections and that the size as well. Those, the increasing number of the tunnels of the beetle is in lines with the increase of the host sizes.